Biogenic Nanomaterials: A Way Forward in Preventing Bacterial Infections: Nanobiotechnology against resistant pathogens - Maham Khan; Shahid Wahab; Haroon Muhammad Ali; Sadia Khan; Reema Iqbal; Tariq Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Antibiotic resistance puts a tremendous strain on the healthcare system. Bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa that cause diseases like endocarditis, pneumonia, and Urinary tract infections have now become resistant to many previously used antibiotics. Antibiotic overuse must be reduced as it has become a public health threat paving the way to pandemics. Instead of creating new antibiotics, repurposing existing medicines that have faced resistance is one way forward. Plant-based antimicrobials have been explored as antibiotics to boost or augment the capability of existing antibiotics. It has been proposed that conjugates of plant-based products and antibiotics have increased activity and that the conjugated groups could help circumvent the beta-lactam antibiotic resistance mechanisms. Antibiotics have been combined with plant-based substances like Berberine, and a considerable synergy has been reported among them. Nanomaterials also promise a powerful environment-friendly strategy for weaponizing antibiotics with plant compounds. Nanoparticles could attach with many biological molecules such as DNA, enzymes, ribosomes, and lysosomes, further affecting the permeability of the cell membrane. The interaction of nanoparticles with many biological targets makes it hard for bacteria to develop resistance against them. Low molecular weight nanomaterial based on antibiotics could be very effective against multidrug-resistant gram-negative pathogens. Our study aims to analyze the progress done at the front of nanomaterials and nano-antibiotics against infectious diseases.